Guyana's Racial Politics: Causes, Issues, and its Welcoming of Western Neocolonialism - Brittney Bahadoor (Caribbean Studies Students' Union, 2023)
This paper discusses the history of ethnopolitics in Guyana and how the racial divide between the two largest ethnic groups in the country-the Indo-Guyanese and Afro-Guyanese-not only fractured society but allowed for Western superpowers to exert neocolonial influence. It explores the historical origins of race relations between the Indians and Africans in Guyana from the time of British colonization to the modern political era of the 196 0s. It looks at how politics was utilized both as unifying factor and a dividing factor-dependent on the goals the political leaders sought after. This article breaks down the ever-complicated political parties and their general history and discusses the causes of this political divide, both due to internal pressures and external forces. It also aims to show how the racial politics in Guyana were orchestrated by both the United States and Great Britain as it occurred during the ushering in of the neocolonial era. It is built around the argument that the racial divide caused by the Guyanese politics of the 1960s became the basis for the complicated modern day race relations and the various causes. The goal is to essentially tell part of the racial and political history of Guyana in a way that is accessible to everyone. Guyana is a country with such a deep history which is often times obscured, this article aims to dissect just a portion of it, especially a part that has affected and continues to affect the population and diaspora even today.